The Organizational Learning Audit - Pace, R. Wayne (Management Communication Quarterly, 2002)
Notes that organizational communication and organizational learning share a common focus on how message processing occurs in institutional settings and how they affect and are affected by people and relationships. Proposes that the assessment of organizational learning represents an assessment of a subset of communication processes in an organization. Examines alternative ways in which organizational learning can be assessed. (PM)
Keywords: formation des adultes